Polyester film and use of the same

JP2025023204APending Publication Date: 2025-02-14TOYOBO CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024209804
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2017-09-29
Filing Date
2024-12-02
Publication Date
2025-02-14

AI Technical Summary

Benefits of technology

【0010】 本発明により、スリット端面の髭状物の少ないポリエステルフィルムロールを提供でき、欠点となる因子を減らすことができたことで、光学用途、特に偏光子保護フィルムへの適用がより可能となる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025023204000001
    Figure 2025023204000001
  • Figure 2025023204000002
    Figure 2025023204000002
Patent Text Reader

Abstract

To provide a polyester film that is suitably used as a polarizer protective film by decreasing the number of whisker-like defects present on a slit end face of the film.SOLUTION: The polyester film has at most one whisker-like substance present per 100 μm film length, the whisker-like substance protruding to a length of 5 μm or more on an end face of the film slit along a mechanical flow direction in the production process of the film. A polyester film for a polarizer protective film is provided, which shows an in-plane retardation of 3000 nm or more and 30000 nm or less. A polarizing plate and a liquid crystal display device are disclosed in which the above film is used.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyester film which is slit along the machine flow direction during film production and has few whisker-like defects on the slit end faces, and more specifically to a polyester film for polarizer protective film which has few whisker-like defects on the slit end faces, and a polarizing plate and a liquid crystal display device using the same. [Background technology]

[0002] Polarizing plates used in liquid crystal displays (LCDs) are usually constructed by sandwiching a polarizer made of polyvinyl alcohol (PVA) or the like dyed with iodine between two polarizer protective films, and triacetyl cellulose (TAC) films are usually used as the polarizer protective films. In recent years, as LCDs have become thinner and their costs have been reduced, there has been a demand for thinner polarizing plates. However, when the thickness of the TAC film used as the polarizer protective film is reduced for this purpose, problems arise in that it is not possible to obtain sufficient mechanical strength and moisture permeability is deteriorated. In addition, TAC films are very expensive, and there is a strong demand for cheaper alternative materials.

[0003] Although polyester films are more durable than TAC films, they have birefringence, unlike TAC films, and therefore have the problem that when they are used as polarizer protective films, image quality is degraded due to optical distortion. That is, since polyester films having birefringence have a certain optical anisotropy (retardation), when they are used as polarizer protective films, rainbow-like color spots are generated when observed from an oblique direction, and image quality is degraded. Therefore, in Patent Document 1, a measure against color spots is taken by controlling the in-plane retardation of the polyester film within a specific range.

[0004] In addition, in the manufacture of TAC films and polyester films in which the molecules are oriented in the stretching direction, both ends in the width direction have an uneven thickness, and are cut off by a cutting device (slitter) after manufacture (slitting process). However, the orientation of the molecular chains that make up the film is a disadvantage, and whiskers and fuzz appear at the slit ends of the film, causing problems such as an increase in foreign matter and film breakage during cutting. For this reason, Patent Document 2 proposes a method for solving the above problems using a cutting technique.

[0005] On the other hand, when producing polyester film, waste film is generated. Methods for reusing or recycling waste film such as film ends cut and removed from products have been attempted. However, when a film having a coating layer of an easy-adhesion resin or an antistatic resin is recycled and the main component is a recycled polyester raw material, there is a problem that the components of the coating layer contained therein are thermally deteriorated, and the obtained film becomes significantly colored or cloudy. Therefore, Patent Document 3 proposes a method for obtaining a polyester film that contains self-recovered raw materials and is transparent and less colored.

[0006] However, in Patent Document 2, there is no knowledge on polyester film, and it is doubtful whether it can be applied. Furthermore, in Patent Document 3, when considering application to optical applications, the hurdle of internal foreign matter generation due to the addition of self-recovered raw materials is high, and in the composition of the coating layer, which has become complicated (diversified) in recent years, the inclusion of crosslinked components and the like hinders recovery and causes internal foreign matter. In addition, after removing the coating layer of the polyester film, which is the self-recovered raw material, by any method, only the base polyester film is left, and from this, a complicated separate process of melt extrusion and pelletization is required to obtain recycled raw material. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] International Publication No. 2011 / 162198 [Patent Document 2] JP 2017-109262 A [Patent Document 3] JP 2013-039764 A Summary of the Invention [Problem to be solved by the invention]

[0008] The present invention has been made in view of the problems in the prior art. That is, an object of the present invention is to eliminate the above-mentioned drawbacks, and in particular to provide a polyester film suitable for use as a polarizer protective film by reducing the number of whisker defects present on the slit end faces of the film.

[0009] The present inventors conducted extensive research to achieve this object and arrived at the present invention. That is, the present invention has the following configuration. 1. The number of whiskers protruding 5μm or more on the edge of the film slit along the machine flow direction during film production is within one per 100μm of film length. The thickness variation rate in the width direction is 5% or less. Polyester film. 2. The polyester film as described in the above 1, having an intrinsic viscosity of 0.55 dl / g or more and 0.65 dl / g or less. 3. The polyester film as described in 1 or 2 above, having a haze value of 2.0% or less and a b value of -0.5 or more and 3.0 or less. 4. The polyester film as described in any one of 1 to 3 above, having a thickness of 15 μm or more and 300 μm or less. 5. The polyester film according to any one of the above items 1 to 4, wherein part of the polyester constituting the polyester film contains a self-recovered polymer generated in the process of producing the polyester film. Item 6. The polyester film according to any one of items 1 to 5 above, having a coating layer on at least one surface thereof. 7. The polyester film according to any one of the above items 1 to 6, which has a laminated structure of three or more layers, including at least surface layers made of polyester on both sides of an intermediate layer made of polyester, and the intermediate layer contains a self-recovered polymer generated in the process of producing the polyester film. 8. The polyester film according to any one of items 1 to 7 above, which has a laminate structure of three or more layers, including at least surface layers made of polyester on both sides of an intermediate layer made of polyester, and the intrinsic viscosity of the polyester constituting the intermediate layer is lower than the intrinsic viscosity of the polyesters constituting both surface layers. 9. The polyester film for polarizer protective film according to any one of the above 1 to 8, which has an in-plane retardation of 3,000 nm or more and 30,000 or less. 10. A polarizing plate comprising a polarizer and the polyester film for use as a polarizer protective film as described in 9 above laminated on at least one surface of the polarizer. 11. A liquid crystal display having a backlight, a liquid crystal cell, and polarizing plates arranged on both sides of the liquid crystal cell, wherein the polarizing plate on at least one side is the polarizing plate described in 10 above. Effect of the Invention

[0010] According to the present invention, a polyester film roll having less whisker-like particles on the slit end surface can be provided, and the factors that cause defects can be reduced, making the film more applicable to optical applications, particularly to polarizer protective films. BEST MODE FOR CARRYING OUT THEINVENTION

[0011] The present invention will be described in detail below.

[0012] (Polyester film) The polyester film in the present invention is a film made of a polyester resin, and is preferably a polyester film mainly composed of at least one selected from polyethylene terephthalate, polypropylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate. It may also be a film made of a copolymer polyester in which a third component monomer is copolymerized with the above-mentioned polyester. Among these polyester films, a polyethylene terephthalate film is most preferred in terms of the balance between physical properties and cost.

[0013] The polyester film may be a single layer or a multilayer. In addition, as long as the effects of the present invention are achieved, each layer may contain various additives in the polyester resin as necessary. Examples of additives include antioxidants, light resistance agents, gelation inhibitors, organic wetting agents, antistatic agents, ultraviolet absorbers, and surfactants.

[0014] (Coating layer) The polyester film of the present invention preferably has an easily adhesive coating layer laminated on the above-mentioned polyester base film. The coating layer usually contains a binder resin, lubricant particles, a crosslinking agent, a surfactant, etc.

[0015] Examples of the lubricant particles in the coating layer include (1) inorganic particles such as silica, kaolinite, talc, light calcium carbonate, heavy calcium carbonate, zeolite, alumina, barium sulfate, carbon black, zinc oxide, zinc sulfate, zinc carbonate, titanium dioxide, satin white, aluminum silicate, diatomaceous earth, calcium silicate, aluminum hydroxide, hydrated halloysite, magnesium carbonate, and magnesium hydroxide; and (2) organic particles such as acrylic or methacrylic, vinyl chloride, vinyl acetate, nylon, styrene / acrylic, styrene / butadiene, polystyrene / acrylic, polystyrene / isoprene, methyl methacrylate / butyl methacrylate, melamine, polycarbonate, urea, epoxy, urethane, phenol, diallyl phthalate, and polyester. In order to provide the coating layer with an appropriate level of slipperiness, silica is particularly preferably used.

[0016] The average particle size of the lubricant particles is preferably 200 nm or more, more preferably 250 nm or more, even more preferably 300 nm or more, and particularly preferably 350 nm or more. When the average particle size of the lubricant particles is 200 nm or more, the particles are less likely to aggregate and lubricity can be ensured, which is preferable.

[0017] The average particle size of the lubricant particles is preferably 2000 nm or less, more preferably 1500 nm, further preferably 1000 nm, and particularly preferably 700 nm. When the average particle size of the lubricant particles is 2000 nm or less, transparency is maintained and the particles do not fall off, which is preferable.

[0018] The lubricant particles may be surface-treated. Surface treatment methods include physical surface treatments such as plasma discharge treatment and corona discharge treatment, and chemical surface treatments using coupling agents, with the use of coupling agents being preferred. As coupling agents, organoalkoxymetal compounds (e.g., titanium coupling agents, silane coupling agents) are preferably used. When the lubricant particles, which are inorganic ultrafine particle fillers, are silica, treatment with a silane coupling agent is particularly effective. Surface treatment may be carried out before the preparation of the coating solution, or the use of additives during the preparation of the coating solution may be used. Alternatively, the compound may be added as such and contained in the coating layer.

[0019] The binder resin constituting the coating layer is not particularly limited as long as it is a resin that provides easy adhesion, but specific examples of polymers include polyester resin, acrylic resin, urethane resin, polyvinyl resin (polyvinyl alcohol, etc.), polyalkylene glycol, polyalkyleneimine, methyl cellulose, hydroxycellulose, starch, etc. Among these, it is preferable to use polyester resin, acrylic resin, and urethane resin from the viewpoint of particle retention and adhesion. In addition, polyester resin is optimal when considering compatibility with polyester film. These binder resins may be used in combination.

[0020] The polyester resin may be present in the coating layer at 100% by mass of the total solid components, but is preferably present at 10% by mass to 90% by mass. More preferably, it is present at 20% by mass to 80% by mass. When the content of the polyester resin is 90% or less, adhesion to a hard coat layer or the like under high temperature and high humidity is maintained, which is preferable. On the other hand, when the content is 10% by mass or more, adhesion to a polyester film under normal temperature and high temperature and high humidity is maintained due to the presence of other urethane resins, etc., which is preferable.

[0021] In the present invention, the coating layer may be formed containing a crosslinking agent in order to form a crosslinked structure in the coating layer. By including a crosslinking agent, it is possible to further improve adhesion under high temperature and high humidity. Specific crosslinking agents include urea-based, epoxy-based, isocyanate-based, oxazoline-based, carbodiimide-based, etc. Among these, melamine-based, isocyanate-based, oxazoline-based, and carbodiimide-based crosslinking agents are preferred in terms of the stability over time of the coating liquid and the effect of improving adhesion under high temperature and high humidity treatment. In addition, a catalyst or the like can be appropriately used as necessary to promote the crosslinking reaction.

[0022] The content of the crosslinking agent in the coating layer is preferably 5% by mass or more and 50% by mass or less based on the total solid content. More preferably, it is 10% by mass or more and 40% by mass or less. When it is 5% by mass or more, the strength of the resin in the coating layer is maintained, and there is no risk of the adhesion being reduced under high temperature and high humidity, which is preferable. On the other hand, when it is 50% by mass or more, the flexibility of the resin in the coating layer is maintained, and the adhesion is maintained at room temperature and under high temperature and high humidity, which is preferable.

[0023] The content of the lubricant particles in the coating layer is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and even more preferably 1% by mass or more. When the content of the lubricant particles in the coating layer is 0.1% by mass or more, it is preferable because an appropriate level of slipperiness is maintained.

[0024] The content of the lubricant particles in the coating layer is preferably 20% by mass or less, more preferably 15% by mass or less, and even more preferably 10% by mass or less. When the content of the lubricant particles in the coating layer is 20% by mass or less, the haze is kept low, which is preferable in terms of transparency.

[0025] The thickness of the coating layer is preferably 0.001 μm or more, more preferably 0.01 μm or more, further preferably 0.02 μm or more, and particularly preferably 0.05 μm or more. When the coating layer has a thickness of 0.001 μm or more, the adhesion is good, which is preferable.

[0026] The thickness of the coating layer is preferably 2 μm or less, more preferably 1 μm or less, further preferably 0.8 μm or less, and particularly preferably 0.5 μm or less. When the thickness of the coating layer is 2 μm or less, there is no risk of blocking occurring, which is preferable.

[0027] The coating layer contains a surfactant to improve leveling during coating and to degas the coating solution. The surfactant may be any of cationic, anionic, and nonionic surfactants, but silicone, acetylene glycol, and fluorine-based surfactants are preferred. These surfactants are preferably contained in the coating layer to the extent that they do not impair the iridescent color suppression effect or adhesion under fluorescent lamps.

[0028] In order to impart other functionality to the coating layer, various additives may be added within a range that does not impair the effect of suppressing iridescent color under fluorescent lamps or the adhesion, such as fluorescent dyes, fluorescent brightening agents, plasticizers, ultraviolet absorbers, pigment dispersants, foam inhibitors, defoamers, preservatives, etc.

[0029] As a coating method, either a so-called in-line coating method in which coating is performed simultaneously with the formation of a polyester film or a so-called off-line coating method in which coating is performed using a separate coater after the polyester film is formed can be used, but the in-line coating method is more efficient and more preferable.

[0030] Any known method can be used to apply the coating solution to the polyester film. For example, reverse roll coating, gravure coating, kiss coating, die coater, roll brush, spray coating, air knife coating, wire bar coating, pipe doctor, impregnation coating, curtain coating, etc. These methods can be used alone or in combination.

[0031] In the present invention, a method for providing a coating layer on a polyester film includes a method of coating a coating liquid containing a solvent, particles, and a resin on a polyester film and drying the coating liquid. Examples of the solvent include an organic solvent such as toluene, water, or a mixture of water and a water-soluble organic solvent, but from the viewpoint of environmental issues, water alone or a mixture of water and a water-soluble organic solvent is preferred.

[0032] The solid content of the coating liquid varies depending on the type of binder resin and the type of solvent, but is preferably 2% by mass or more, more preferably 4% by mass or more. The solid content of the coating liquid is preferably 35% by mass or less, more preferably 15% by mass or less.

[0033] The drying temperature after coating also depends on the type of binder resin, the type of solvent, the presence or absence of a crosslinking agent, the solids concentration, etc., but is preferably 80° C. or higher and 250° C. or lower.

[0034] The surface roughness (Ra) of the coating layer is related to the slipperiness of the coating layer surface, and is preferably 0.01 nm or more, more preferably 0.1 nm or more, even more preferably 0.2 nm or more, and particularly preferably 0.5 nm or more. On the other hand, the upper limit of the surface roughness (Ra) of the coating layer is preferably 200 nm or less, more preferably 100 nm or less, even more preferably 80 nm or less, and particularly preferably 50 nm or less.

[0035] (Manufacture of polyester film) The polyester film of the present invention can be produced according to a general method for producing a polyester film, for example, a method in which a polyester resin is melted, extruded into a sheet, and a non-oriented polyester sheet or film is stretched in the longitudinal direction by utilizing a speed difference between rolls at a temperature equal to or higher than the glass transition temperature, if necessary, or the transverse direction is stretched in a tenter at a temperature equal to or higher than the glass transition temperature without the longitudinal stretching, and then heat-treated.

[0036] The polyester film of the present invention is believed to be applicable in a wide range of applications, but is suitably applied to optical films, particularly polarizer protective films.

[0037] The polyester film for protecting a polarizer may be either a uniaxially stretched film or a biaxially stretched film. However, when a biaxially stretched film is used as a polarizer protective film, depending on the in-plane retardation of the film, rainbow-like color spots may not be observed when observed from directly above the film surface, but rainbow-like color spots may be observed when observed from an oblique direction, so care must be taken.

[0038] This phenomenon occurs because the biaxially stretched film is made of an index ellipsoid with different refractive indices in the running direction, width direction, and thickness direction, and there exists a direction where the retardation becomes zero (the index ellipsoid appears as a perfect circle) depending on the light transmission direction inside the film. Therefore, when the liquid crystal display screen is observed from a specific oblique direction, a point where the retardation becomes zero may be generated, and rainbow-like color spots will appear concentrically around that point. If the angle from directly above the film surface (normal direction) to the position where the rainbow-like color spots are visible is θ, this angle θ becomes larger as the birefringence in the film surface increases, and the rainbow-like color spots become less visible. Since the angle θ tends to be smaller in biaxially stretched films, uniaxially stretched films are preferable because the rainbow-like color spots are less visible.

[0039] However, in a completely uniaxial (single-axis symmetric) film, the mechanical strength in the direction perpendicular to the orientation direction may be significantly reduced, so in the present invention, it is also preferable that the film has biaxiality (biaxial symmetry) to the extent that it does not substantially produce rainbow-like color spots or does not produce rainbow-like color spots within the viewing angle range required for the liquid crystal display screen.

[0040] The polyester film used for the polarizer protective film preferably has an in-plane retardation of 3000 to 30000 nm. If the in-plane retardation is 3000 nm or more, when the film is used as a polarizer protective film, it is preferable that the film does not show strong interference color when observed from an oblique direction and can ensure good visibility. The lower limit of the in-plane retardation is preferably 4500 nm, more preferably 5000 nm, even more preferably 6000 nm, particularly preferably 8000 nm, and most preferably 10000 nm.

[0041] On the other hand, the preferred upper limit of the in-plane retardation is 30000 nm. Even if a polyester film having an in-plane retardation exceeding 30000 nm is used, the effect of further improving visibility is substantially saturated. In addition, if the film has an in-plane retardation of 30000 nm or less, the thickness of the film is not too thick, and the handling property as an industrial material is good, which is preferable.

[0042] In addition, the in-plane retardation in the present invention can be obtained by measuring the refractive index and thickness in two axial directions, or can be obtained by using a commercially available automatic birefringence measuring device such as KOBRA-21ADH (Oji Scientific Instruments Co., Ltd.). The wavelength for measuring the refractive index is 589 nm.

[0043] Specifically, the film-forming conditions of the polyester film of the present invention are as follows: the longitudinal stretching temperature and the transverse stretching temperature are preferably 80 to 130°C, and more preferably 90 to 120°C. The longitudinal stretching ratio is preferably 1.0 to 3.5 times, and more preferably 1.0 to 3.0 times. The transverse stretching ratio is preferably 2.5 to 6.0 times, and more preferably 3.0 to 5.5 times. In order to control the in-plane retardation, it is preferable to control the ratio between the longitudinal stretching ratio and the transverse stretching ratio. Increasing the difference between the longitudinal and transverse stretching ratios is preferable because it can increase the retardation. Setting the stretching temperature low is also a preferable measure for increasing the retardation. In the subsequent heat treatment, the treatment temperature is preferably 100 to 250°C, and more preferably The temperature is preferably 180 to 245°C.

[0044] In order to suppress the variation of retardation, it is preferable that the thickness unevenness of the film is small. Since the stretching temperature and the stretching ratio affect the thickness unevenness of the film, it is preferable to optimize the film formation conditions from the viewpoint of the thickness unevenness.

[0045] The thickness unevenness of the film of the present invention is preferably 5.0% or less, more preferably 4.5% or less, even more preferably 4.0% or less, and particularly preferably 3.0% or less.

[0046] As described above, in order to control the in-plane retardation of the film to a specific range, the stretching ratio, the stretching temperature, and the thickness of the film can be appropriately set. For example, the greater the difference in the stretching ratio between the longitudinal and transverse directions, the lower the stretching temperature, and the thicker the film, the easier it is to obtain a high in-plane retardation. Conversely, the smaller the difference in the stretching ratio between the longitudinal and transverse directions, the higher the stretching temperature, and the thinner the film, the easier it is to obtain a low retardation. However, if the thickness of the film is increased, the thickness direction phase difference tends to increase. Therefore, it is desirable to appropriately set the film thickness within the range described below. In addition to controlling the in-plane retardation, it is preferable to set the final film-forming conditions taking into account the physical properties required for processing.

[0047] The thickness of the polyester film of the present invention is arbitrary, but is preferably in the range of 15 to 300 μm, more preferably in the range of 20 to 200 μm, and even more preferably in the range of 30 to 150 μm. Even if the film has a thickness of less than 15 μm, it is possible in principle to obtain a retardation of 3000 nm or more. However, in that case, the anisotropy of the mechanical properties of the film becomes significant, and it is easy to cause tears, breaks, etc., and the practicality as an industrial material is likely to decrease, which is not very preferable. A particularly preferable lower limit of the thickness is 35 μm. On the other hand, if the upper limit of the thickness of the polarizer protective film is 300 μm or less, it is preferable because the thickness of the polarizing plate does not become too thick. From the viewpoint of practicality as a polarizer protective film, the upper limit of the thickness is preferably 200 μm. A particularly preferable upper limit of the thickness is 100 μm, which is about the same as that of a general TAC film. In order to control the in-plane retardation within the range of the present invention even within the above thickness range, the polyester constituting the film is preferably polyethylene terephthalate.

[0048] In order to suppress deterioration of optically functional dyes such as iodine dyes, the polyester film in the present invention preferably has a light transmittance of 20% or less at a wavelength of 380 nm. The light transmittance of 380 nm is more preferably 15% or less, even more preferably 10% or less, and particularly preferably 5% or less. If the light transmittance is 20% or less, deterioration of the optically functional dye caused by ultraviolet rays can be suppressed. The transmittance in the present invention is measured in a direction perpendicular to the plane of the film, and can be measured using a spectrophotometer.

[0049] In order to make the transmittance of the polyester film of the present invention at a wavelength of 380 nm 20% or less, it is desirable to appropriately adjust the type and concentration of the ultraviolet absorber contained in the polyester film and the thickness of the film. The ultraviolet absorber used in the present invention is a known substance. Examples of ultraviolet absorbers include organic ultraviolet absorbers and inorganic ultraviolet absorbers, and from the viewpoint of transparency, organic ultraviolet absorbers are preferred. Examples of organic ultraviolet absorbers include, but are not limited to, benzotriazole-based, benzophenone-based, cyclic imino ester-based, and combinations thereof. However, from the viewpoint of durability, benzotriazole-based and cyclic imino ester-based are particularly preferred. When two or more types of ultraviolet absorbers are used in combination, ultraviolet rays of different wavelengths can be absorbed simultaneously, so that the ultraviolet absorption effect can be further improved. can be done.

[0050] Examples of the ultraviolet absorber include benzophenone-based ultraviolet absorbers, benzotriazole-based ultraviolet absorbers, and acrylonitrile-based ultraviolet absorbers include 2-[2'-hydroxy-5'-(methacryloyloxymethyl)phenyl]-2H-benzotriazole, 2-[2'-hydroxy-5'-(methacryloyloxyethyl)phenyl]-2H-benzotriazole, 2-[2'-hydroxy-5'-(methacryloyloxypropyl)phenyl]-2H-benzotriazole, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, 2,4-di-tert-butyl-6-(5-chlorobenzotriazol-2-yl)phenol, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, and 2-(5-chloro(2H)-benzotriazol-2-yl)-4-methyl-6-(tert-butyl)phenol. Examples of the cyclic imino ester ultraviolet absorbers include 2,2'-(1,4-phenylene)bis(4H-3,1-benzoxazinon-4-one), 2-methyl-3,1-benzoxazin-4-one, 2-butyl-3,1-benzoxazin-4-one, 2-phenyl-3,1-benzoxazin-4-one, etc. However, the present invention is not limited to these.

[0051] The method of incorporating the ultraviolet absorber into the polyester film of the present invention may be a combination of known methods. For example, the ultraviolet absorber may be blended in advance with a dried ultraviolet absorber and a polymer raw material using a kneading extruder to prepare a master batch, and then the master batch and the polymer raw material are mixed during film formation.

[0052] In this case, the concentration of the ultraviolet absorber in the master batch is preferably 5 to 30% by mass in order to disperse the ultraviolet absorber uniformly and to compound economically. As conditions for preparing the master batch, it is preferable to use a kneading extruder and extrude for 1 to 15 minutes at an extrusion temperature of the melting point of the polyester raw material or higher and 290°C or lower. If the temperature is 290°C or higher, the weight loss of the ultraviolet absorber is large and the viscosity of the master batch is significantly reduced. If the extrusion temperature is 1 minute or less, it becomes difficult to mix the ultraviolet absorber uniformly. At this time, a stabilizer, a color tone adjuster, and an antistatic agent may be added as necessary.

[0053] In the present invention, the polyester film is preferably a multi-layer structure of at least three layers, and an ultraviolet absorber is preferably added to the intermediate layer of the film. A polyester film having a three-layer structure containing an ultraviolet absorber in the intermediate layer can be specifically produced as follows. A polyester pellet alone for both surfaces, and a master batch containing an ultraviolet absorber and a polyester pellet for the intermediate layer are mixed in a predetermined ratio, dried, and then fed to a known melt lamination extruder, extruded from a slit-shaped die into a sheet, and cooled and solidified on a casting roll to produce an unstretched film. That is, two or more extruders, three or more manifolds or merging blocks (e.g., merging blocks having a square merging portion) are used to laminate the film layers constituting both surface layers and the intermediate layer, and a three or more layer sheet is extruded from a die and cooled on a casting roll to produce an unstretched film. In the present invention, in order to remove foreign matter contained in the raw polyester that causes optical defects, it is preferable to perform high-precision filtration during melt extrusion. The filtration particle size (initial filtration efficiency 95%) of the filter medium used for high-precision filtration of molten resin is preferably 15 μm or less. When the filtration particle size of the filter medium is 15 μm or less, foreign matter of 20 μm or more can be sufficiently removed, which is preferable.

[0054] It is preferable that self-recovered polymer raw materials are used for the polyester film of the present invention. I wish.

[0055] Here, we will explain the method for producing self-recovering raw materials. The scrap film at the end of the film, which was slit in the machine flow direction from the product and cut off, was crushed and dried at the glass transition temperature of about 160°C to remove moisture. The dried crushed film was melted in an extruder and extruded from a die in the form of strands, which were then rapidly cooled and solidified in cold water. The solidified strands were cut into pellets with a strand cutter, and the surface was dried to prevent fusion, obtaining self-recovering pellets.

[0056] The moisture content after drying is preferably 10 ppm or less. If the moisture content is 10 ppm or less, the hydrolysis of the polymer is unlikely to be accelerated, and there is no risk of a decrease in the intrinsic viscosity, which is preferable.

[0057] Both ends of the film of the master roll are usually cut off because the film thickness is uneven and the film quality is poor due to the effects of clip marks made during transport in the tenter. However, when these portions are recovered and used as self-recovered raw material, caution is required because, depending on the coating layer laminated on the cut portions, the polyester film produced from this self-recovered raw material may become contaminated with foreign matter, become discolored, or become cloudy.

[0058] In the present invention, the coating layer on both end portions of the master roll that is slit and cut off is different from the coating composition for laminating a coating layer having properties such as easy adhesion required for the product polyester film that is suitably used for the polarizer protective film described above, and is coated separately without overlapping with the coating layer laminated on the product polyester film as a separate coating composition that is less likely to cause contamination, coloring or turbidity even if it is re-introduced as part of the raw polyester material for the product polyester film, and it is preferable to cut off the portions located at both ends in the width direction of such master roll up to the portions where a separate coating liquid has been applied, and use them as self-recoverable raw material.

[0059] The coating liquid to be applied separately at both ends in the width direction of the film is not particularly limited as long as it has a composition that allows for the preparation of self-recoverable raw materials. However, in consideration of the stability and safety of the composition used, it is preferable that the coating liquid be a resin composition mainly composed of water.

[0060] The aqueous coating solution may contain a small amount of organic solvent to improve the stability of the coating solution. Examples of the organic solvent include methyl ethyl ketone, acetone, ethyl acetate, tetrahydrofuran, dioxane, cyclohexanone, n-hexane, toluene, xylene, methanol, ethanol, 1-propanol, and 2-propanol. A plurality of organic solvents may be included.

[0061] The above-mentioned aqueous coating liquid may contain known additives, such as a heat stabilizer, an oxidation stabilizer, a weathering stabilizer, an ultraviolet absorber, an organic lubricant, and organic or inorganic fine particles, within the range that does not impair the effects of the present invention.

[0062] Any known coating method may be used, including, for example, reverse coating, gravure coating, microgravure coating, rod coating, die coating, roll coating, roll brushing, spray coating, air knife coating, curtain coating, and the like.

[0063] In the present invention, the separate coating layer on both ends in the film width direction is applied to at least one side of the polyester film, but it is applied before the crystal orientation of the polyester film is completed, and then the polyester film is stretched in at least one direction, and then the crystal orientation of the polyester film is completed. This makes it possible to more significantly exhibit the effects of the present invention. Therefore, this is the preferred method.

[0064] The amount of coating is 1 m 2The thickness of the final dry coating film is preferably 0.001 μm or more, more preferably 0.01 μm or more, even more preferably 0.02 μm or more, and particularly preferably 0.05 μm or more. When the coating layer has a thickness of 0.001 μm or more, the slipperiness can be sufficiently ensured, the slipperiness to the film roll is improved, and a film roll with few defects such as scratches can be obtained.

[0065] The thickness of the coating layer is preferably 2 μm or less, more preferably 1 μm or less, further preferably 0.8 μm or less, and particularly preferably 0.5 μm or less. When the thickness of the coating layer is 2 μm or less, there is no risk of blocking occurring, which is preferable.

[0066] In the present invention, after the aqueous coating liquid is applied to the polyester substrate, a drying and stretching treatment is carried out. This drying is preferably carried out at a temperature of 80° C. or higher and 250° C. or lower, although this depends on the type of binder resin, the type of solvent, the presence or absence of a crosslinking agent, the solids concentration, etc. The stretching treatment is performed according to the above-mentioned polyester film production method, and it is preferable to carry out the treatment under conditions corresponding thereto.

[0067] In addition to the above, self-recovered raw materials can also be produced by peeling off the coating layer from edge rolls at the ends of slit rolls or off-grade rolls that do not meet product standards.

[0068] There is no particular limitation on the method for peeling off the coating layer, so long as it does not cause problems such as foreign matter being mixed into the film after peeling. One method is to chemically and physically peel off only the coating layer, such as sandblasting, leaving only the resin layer, and this method may also be applied in the present invention.

[0069] The polyester film for polarizer protective film in the present invention preferably has a b-value indicating a yellowish-blueish tinge of about zero even when self-recycling raw materials are used. When the b-value is 3.0 or less, the film does not look yellowish, and when applied to a polarizer protective film, there are no problems such as deterioration of image quality or discoloration, which is preferable. In addition, when the b-value is -0.5 or more, the film does not look blue, and there is no dark impression, which is preferable.

[0070] The haze of the film is also preferably 2.0% or less. If the haze is 2.0% or less, transparency is maintained and there is no risk of causing display problems such as liquid crystal display, which is preferable.

[0071] The intrinsic viscosity of the polyester film obtained by the present invention is preferably 0.55 dl / g or more, more preferably 0.56 dl / g or more, and even more preferably 0.57 dl / g or more. When the intrinsic viscosity is 0.55 dl / g or more, the mechanical strength of the film is maintained and there is no risk of problems occurring in film formation stability and breakage resistance, which is preferable.

[0072] The intrinsic viscosity of the polyester film obtained by the present invention is preferably 0.65 dl / g or less, more preferably 0.64 dl / g or less, and even more preferably 0.63 dl / g or less. When the intrinsic viscosity is 0.65 dl / g or less, the film does not become too hard and cutting defects are unlikely to occur when both ends of the film in the width direction are cut off with a slitter, which is preferable because the cutting quality and cutting state are good.

[0073] Here, the intrinsic viscosity of the produced polyester film is determined by dividing the polyester film into a specific By dissolving it in a solvent and evaluating the solution in a viscosity tube, the intrinsic viscosity (dl / l) can be obtained. Cut.

[0074] In the polyester film of the present invention, the number of whiskers (including cutting irregularities such as burrs and fluff) protruding 5 μm or more from the slit end face is preferably one or less per 100 μm of film length.

[0075] In polyester film, the number of whisker-like features (cut defects) protruding 5 μm or more from the film edge is one or less per 100 μm of film length, which means that the edge of the film slit by a slitter in the machine direction is observed with an electron microscope or optical microscope, and the number of whisker-like features (cut defects) protruding 5 μm or more from the edge per 100 μm of film length is counted to be one or less.

[0076] If these whiskers (cutting defects) are less than 5 μm in size and protrude from the edge surface, they do not significantly affect the incorporation or adhesion of foreign matter during transportation and handling when applied to the polarizer protective film, and in the unlikely event that foreign matter does adhere, it is easy to remove, so they do not need to be a particular problem.

[0077] In order to obtain a polyester film of the present invention in which whisker-like features (cutting defects) protruding 5 μm or more from the slit edge are less than one per 100 μm of film length, the slitting method is not particularly limited as long as it is a method that can obtain the film edge of the present invention, but preferred examples include a method that uses a laser beam as the slitting means (a method in which a beam is irradiated onto the film surface with a laser beam oscillator, and the film is instantly melted or evaporated by the laser irradiation energy to slit along the scanning trajectory of the beam, and various oscillators such as a carbon dioxide laser, an argon laser, a YAG laser, etc. are used for irradiating the laser beam), a method of slitting with a blade (Thomson blade, rotary blade, etc.), etc.

[0078] When using a blade (Thomson blade, rotary blade, etc.) to slit the film, the blade must be replaced or the blade edge must be renewed under certain conditions. For example, when slitting polyester film, if the cutting area is 200 m 2Not exceeding 160m, preferably 2 The polyester film of the present invention can be obtained by replacing the blade or updating the blade edge so that the cutting speed does not exceed 151 m / min. For example, when a 100 μm film is slit at a speed of 150 m / min for 7 consecutive days, 2 At this point, it is preferable to replace the blade or renew the blade edge.

[0079] The amount of self-recovery raw material added is not particularly limited as long as it satisfies the above-mentioned film characteristics, but the mass ratio of the layer of the film to which the self-recovery raw material is added to the total raw materials is preferably 3 mass% or more, more preferably 5 mass% or more, even more preferably 7 mass% or more, and particularly preferably 8 mass% or more. If it is 3 mass% or more, it is preferable because the intrinsic viscosity of the obtained film is easily adjusted to 0.65 dl / g or less, the elastic modulus of the film is not too high, and whiskers protruding from the end surface are reduced.

[0080] The amount of self-recovery raw material added is not particularly limited as long as it satisfies the above-mentioned film characteristics, but the mass ratio of the layer to which the self-recovery raw material of the film is added to the total raw materials is preferably 30 mass% or less, more preferably 28 mass% or less, even more preferably 26 mass% or less, and particularly preferably 25 mass% or less. If it is 30 mass% or less, the intrinsic viscosity of the film is likely to be 0.55 dl / g or more, the mechanical strength of the film is maintained, and it is preferable in terms of film formation stability, breakage resistance, etc.

[0081] The polyester film of the present invention has reduced whisker-like particles on the slit end faces. It has been found that the intrinsic viscosity of the resin during film molding is related to the reduction in the number of whiskers, and by controlling the intrinsic viscosity of the resin within a certain range, the whiskers on the slit end faces can be preferably reduced.

[0082] In terms of the strength of the resulting polyester film, a certain level of intrinsic viscosity of the polyester constituting the film is desirable, and in order to achieve this, it is preferable to have a laminate structure of three or more layers having at least surface layers made of polyester on both sides of an intermediate layer made of polyester, both surface layers being polyester layers with relatively high intrinsic viscosity, and the intermediate layer being a polyester layer with relatively low intrinsic viscosity. In particular, it is preferable to configure the intermediate layer by including a self-recovering polymer with low intrinsic viscosity generated in the process of manufacturing the polyester film.

[0083] The intrinsic viscosity of both surface layers of the polyester film having such a laminated structure of three or more layers is preferably 0.63 dl / g or more, more preferably 0.64 dl / g or more, and even more preferably 0.65 dl / g. When the intrinsic viscosity is 0.63 dl / g or more, the intrinsic viscosity of the entire film is not too low, and there is no problem such as breakage during film formation, which is preferable.

[0084] The intrinsic viscosity of both surface layers of the polyester film having such a laminated structure of three or more layers is preferably 0.67 dl / g or less, more preferably 0.66 dl / g or less, and even more preferably 0.65 dl / g. When the intrinsic viscosity is 0.67 dl / g or less, the intrinsic viscosity of the resin is not too high, the pressure applied to the filter during extrusion is not too high, and problems such as poor discharge and uneven thickness are not caused, which is preferable.

[0085] Furthermore, the intrinsic viscosity of the intermediate layer of the polyester film having such a laminated structure of three or more layers is preferably 0.56 dl / g or more, more preferably 0.57 dl / g or more, and even more preferably 0.58 dl / g or more. When the intrinsic viscosity is 0.56 dl / g or more, the intrinsic viscosity of the entire film is not too low, and there are no problems such as breakage during film formation, which is preferable.

[0086] The intrinsic viscosity of the intermediate layer of the polyester film obtained by the present invention is preferably 0.62 dl / g or less, more preferably 0.61 dl / g or less, and even more preferably 0.60 dl / g or less. When the intrinsic viscosity is 0.62 dl / g or less, the intrinsic viscosity of the resin is not too high, the pressure applied to the filter during extrusion is not high, and film formation can be performed without causing discharge defects, so that the target thickness is easily controlled and thickness unevenness is small.

[0087] Here, the intrinsic viscosity (dl / g) can be calculated from the fluid viscosity obtained from an online viscometer such as a capillary viscometer installed in the piping during each melt extrusion, the measurement temperature (°C), etc., and the intrinsic viscosity (dl / l) can be obtained using a pre-programmed conversion formula.

[0088] The intrinsic viscosity of the resin can control the intrinsic viscosity of the resulting polyester film and can reduce the occurrence of whiskers, but it is also important in the layer structure of the polyester film. Taking a three-layer polyester structure, excluding any coating layers, as an example, the thickness composition ratio (surface layer: intermediate layer: surface layer) is preferably controlled between 4:92:4 and 13:74:13, and more preferably between 5:90:5 and 10:80:10. If the thickness ratio of both surface layers is 4% or more each, the film haze increases due to the bleed-out of the ultraviolet absorbing agent and other additives added to the intermediate layer. This is preferable.

[0089] When the ratio of each of the two surface layers is 13% or less, the intrinsic viscosity of the resulting polyester film does not become too high, and the effect of inhibiting the generation of whiskers becomes clear, which is preferable.

[0090] In general, a polarizing plate is composed of a polarizer and a polarizer protective film laminated on both sides of the polarizer, and at least one of the polarizer protective films is preferably the polyester film of the present invention. The polarizer is usually a film mainly made of polyvinyl alcohol (PVA) in which iodine compound molecules are adsorbed and aligned.

[0091] In addition, in the present invention, it is also preferable to use a polarizer protective film having various hard coat layers laminated on the surface of the polarizing plate for the purpose of preventing reflection, suppressing glare, suppressing scratches, etc., and it is preferable that the surface having such a hard coat layer is laminated so as to be provided on the side that is not in contact with the polarizer.

[0092] The liquid crystal display device of the present invention is a device in which polarizing plates are arranged on both sides of a liquid crystal cell, and images are displayed by a backlight arranged on one side of the cell, the light source of which is a cold cathode fluorescent lamp (CCFL) or a light emitting diode (LED). It is preferable that the polarizing plate of the present invention is used for at least one of the two polarizing plates. The liquid crystal display device may appropriately have other components other than the above, such as a color filter, a lens film, a diffusion sheet, an anti-reflection film, etc.

[0093] The backlight may be of an edge light type, in which the light guide plate and reflector plate are made of steel members, or of a direct type, but it is preferable to use white LEDs as the backlight light source for the liquid crystal display device. White LED is an element that emits white light by combining a phosphor with an LED that emits blue light or ultraviolet light using a compound semiconductor. Phosphors include yttrium aluminum garnet yellow phosphors and terbium aluminum garnet yellow phosphors, and among them, white LEDs that combine a blue LED using a compound semiconductor with a yttrium aluminum garnet yellow phosphor have a continuous and wide emission spectrum and excellent luminous efficiency, so they are expected to save energy.

[0094] A method that combines LEDs that emit red, green, and blue colors (three-color LED method) has also been put to practical use, but the emission spectrum with this method is narrow and discontinuous. In addition, fluorescent tubes such as CCFLs, which are widely used as conventional backlight light sources, also have a peak at a specific wavelength and a discontinuous emission spectrum, so care must be taken in this regard as the effects of the present invention may not be fully achieved.

[0095] The arrangement of the polarizer protective film of the present invention in the liquid crystal display device is not particularly limited, but in the case of a liquid crystal display device having a polarizing plate arranged on the incident light side (light source side), a liquid crystal cell, and a polarizing plate arranged on the outgoing light side (viewing side), it is preferable to arrange it on the incident light side of the polarizing plate arranged on the incident light side, or on the outgoing light side of the polarizing plate arranged on the outgoing light side, and more preferably to arrange it on the outgoing light side of the polarizing plate arranged on the outgoing light side. If the polarizer protective film of the present invention is arranged in a position other than the above, the polarization characteristics of the liquid crystal cell may be changed. On the other hand, it is preferable to use a film without in-plane retardation, such as a TAC film, an acrylic film, or a norbornene-based resin film, on the surface on which the polarizer protective film of the present invention is not used. EXAMPLES

[0096] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples, and can be practiced with appropriate modifications within the scope of the spirit of the present invention, all of which are included in the technical scope of the present invention.

[0097] The evaluation methods used in the examples and the methods for evaluating various physical properties described in the text are shown below.

[0098] (1) Average particle size [Measurement method using a scanning electron microscope] The average particle size of particles used in coating layers, etc. can be measured by the following method. Particles are photographed with a scanning electron microscope (SEM) and the maximum diameter (the distance between the two most distant points) of 300 to 500 particles is measured at a magnification such that the size of the smallest particle is 2 to 5 mm. The average particle size of the particles present in the coating layer in the present invention can be measured by the above measurement method.

[0099] (2) Intrinsic viscosity of resin In the present invention, the intrinsic viscosity of the resin of each layer is evaluated by evaluating the fluid viscosity during melt molding, and is evaluated using an online viscometer VIS (manufactured by Gneuss) installed in the piping for the molten fluid. The intrinsic viscosity (dl / l) was obtained using a pre-programmed conversion formula.

[0100] (3) Film thickness (d) The thickness d was determined in accordance with JIS K 7130-1999 "Method of measuring thickness of plastic films and sheets (Method A)".

[0101] (4) Refractive index (Nx, Ny, Nz) The refractive index in the MD direction (Nx), the refractive index in the TD direction (Ny), and the refractive index in the thickness direction (Nz) were determined according to JIS K 7142-2014 "Method for measuring the refractive index of plastic films (Method A)". The measurement wavelength was 589 nm.

[0102] (5) Birefringence (ΔNxy), in-plane retardation (Re) Retardation is the phase difference expressed by the product of the birefringence caused by the refractive index (Nx, Ny, Nz) in each axial direction of the film in the thickness direction (Z axis) and two axial directions (x axis, y axis) that are perpendicular to the thickness direction and perpendicular to each other, and the thickness d of the film. Here, it refers to the in-plane retardation, which is the product of the birefringence Nxy caused by light incident on the film surface (xy plane) with MD as the x axis and TD as the y axis, and the thickness d, and each was calculated using the following formula. As is customary, the unit of in-plane retardation is nm. ΔNxy = |Nx-Ny| Re = Nxy / d

[0103] (6) Thickness retardation (Rth) The thickness retardation indicates the retardation caused by light incident in the thickness direction (z-axis) and two axial directions (x-axis, y-axis) perpendicular to the thickness direction and perpendicular to each other with respect to the film surface, and was calculated here as the product of the average of the two birefringences in the xz plane and yz plane and the film thickness d using the following formula. Note that, as is customary, the unit is nm. Rth = (|Nx-Nz|+|Ny-Nz|) / 2×d

[0104] (7) Intrinsic viscosity of the entire film produced and of the raw material pellets In accordance with JIS K 7367-2002 "Plastics - Determination of viscosity of dilute solutions using a capillary viscometer - Part 5: Thermoplastic polyester (TP) homopolymers and copolymers", the viscosity number obtained is measured under the following measurement conditions to determine the viscosity against the mass concentration c of the solution. Based on the numerical relationship, the value when the mass concentration c = 0 was taken as the intrinsic viscosity (iV). Solvent: Phenol / 1,1,2,2-tetrachloroethane=60 / 40(wt%) Tube: Ubbelohde viscosity tube Temperature: 30±0.1℃

[0105] (8) Iridescence observation A polarizer was prepared by attaching the films of the Examples and Comparative Examples prepared by the method described below to one side of a commercially available polarizer so that the absorption axis of the polarizer and the main orientation axis of the film (the higher Nx and Ny) were perpendicular to each other, and attaching a commercially available TAC film to the other side. This was used in a commercially available liquid crystal display device having a liquid crystal cell sandwiched between polarizing plates with a white LED as a backlight and two TAC films as polarizer protective films, with the polarizing plate on the exit light side removed, and the film of the Examples and Comparative Examples was installed on the exit light side, and the liquid crystal display device was visually observed from the front and oblique directions, and the occurrence of rainbow spots was judged as follows. ○: No rainbow spots from any direction ×: When observed from an oblique direction, rainbow spots are clearly observed.

[0106] (9) Thickness variation rate in the width direction A continuous tape-like sample 3m long in the width direction and 5cm long in the length direction is wound up, and the thickness of the film is measured using a continuous film thickness measuring device (manufactured by Anritsu Corporation) and recorded on a recorder. The maximum thickness (dmax), minimum thickness (dmin), and average thickness (d) are obtained from the chart, and the thickness variation rate (%) is calculated using the following formula. The measurement was performed three times, and the average value was calculated. If the length in the width direction is less than 3m, it is joined together. The jointed parts are deleted from the data. Thickness variation rate (%) = ((dmax-dmin) / d) x 100 The average value was calculated as the thickness variation rate (%) in the width direction and was judged according to the following criteria. ○: Thickness variation rate in the width direction is 3% or less △: Thickness variation rate in the width direction is 5% or less ×: Thickness variation in the width direction is more than 5%

[0107] (10) Film transparency (haze) The measurement was performed using a turbidity meter (Nippon Denshoku, NDH2000) in accordance with JIS K 7136-2000 "Determination of haze for plastics and transparent materials."

[0108] (11) Color Tone (b value) The measurements were made using a color difference meter (ZE2000, manufactured by Nippon Denshoku) in accordance with JIS K 7373-2006 "Plastics - Determination of yellowness and discoloration".

[0109] (12) Surface roughness (Ra) In accordance with JIS B 0601-2001 "Geometric Product Specifications (GPS)-Surface Texture; Profile Curve Method-Terminology, Definitions and Surface Texture Parameters", Ra was measured using Surfcom (registered trademark) 304B (manufactured by Tokyo Seimitsu Co., Ltd.) The measurement conditions were cutoff 0.08 μm, stylus radius 2 μm, measurement length 0.8 mm, and measurement speed 0.03 mm / sec.

[0110] (13) Glass transition temperature The glass transition temperature was measured using a differential scanning calorimeter (Seiko Instruments, DSC6200) in accordance with JIS K 7121-2012 "Method for measuring transition temperature of plastics." A 10 mg resin sample was heated at 20°C / min over the temperature range of 25°C to 300°C, and the extrapolated glass transition onset temperature obtained from the DSC curve was taken as the glass transition temperature.

[0111] (14) Number average molecular weight 0.03 g of the resin was dissolved in 10 ml of tetrahydrofuran, and the number average molecular weight was measured using a GPC-LALLS low-angle light scattering photometer (LS-8000, manufactured by Tosoh Corporation) at a column temperature of 30°C, a flow rate of 1 ml / min, and a column (Shodex KF-802, 804, 806, manufactured by Showa Denko K.K.).

[0112] (15) Resin composition The resin was dissolved in deuterated chloroform and subjected to 1H-NMR analysis using a Varian Gemini 200 nuclear magnetic resonance analyzer (NMR), and the molar percentages of each component were determined from the integral ratios.

[0113] (16) Membrane formation stability (membrane permeability) The film was checked for breakage during the process from when the process temperature became stable until a film length of 5,000 m was formed. ○: Stable film formation possible (no breakage occurs) △: Slightly unstable running (may break occasionally) ×: Frequent breakage and inability to produce stable films

[0114] (17) Measurement of whisker marks on film edge The slit end faces of a polyester film slit by a slitter along the machine flow direction were observed under an optical microscope or a scanning electron microscope at a magnification of 500 to 3000 times, and the number of whisker-like protrusions of 5 μm or more per 100 μm at different slit end positions were counted from the images obtained by photographing them, and the counts at 10 positions were averaged to evaluate the number of whisker-like protrusions on the film end face.

[0115] (Production Example 1: Polyethylene terephthalate resin A) The esterification reactor was heated to 200°C, and 86.4 parts by mass of terephthalic acid and 64.4 parts by mass of ethylene glycol were charged. While stirring, 0.017 parts by mass of antimony trioxide, 0.064 parts by mass of magnesium acetate tetrahydrate, and 0.16 parts by mass of triethylamine were charged as catalysts. Then, the temperature was increased under pressure, and a pressurized esterification reaction was carried out under conditions of a gauge pressure of 0.34 MPa and 240°C. After that, the esterification reactor was returned to normal pressure, and 0.014 parts by mass of phosphoric acid was added. Further, the temperature was increased to 260°C over 15 minutes, and 0.012 parts by mass of trimethyl phosphate was added. Then, after 15 minutes, a dispersion treatment was carried out using a high-pressure disperser, and after 15 minutes, the obtained esterification reaction product was transferred to a polycondensation reactor, and a polycondensation reaction was carried out at 280°C under reduced pressure. After the polycondensation reaction was terminated based on the stirring torque, the strands were cooled in cooling water and solidified. The solidified strands were cut into pellets and then dried under reduced pressure to obtain polyethylene terephthalate resin A (hereinafter referred to as resin A) with an intrinsic viscosity of 0.65 dl / g.

[0116] (Production Example 2: Polyethylene terephthalate resin B) The dried UV absorber (2,2'-(1,4-phenylene)bis(4H-3,1-phenylene) 10 parts by mass of benzoxazinon-4-one, 10 parts by mass of the polymer prepared in Production Example 1 that does not contain particles 90 parts by mass of ethylene terephthalate resin A was mixed and extruded using a kneading extruder to obtain polyethylene terephthalate resin B (hereinafter, resin B) containing an ultraviolet absorbing agent and having an intrinsic viscosity of 0.58 dl / g.

[0117] (Production Example 3: Self-recovery polyethylene terephthalate resin C) The scrap film at the end of the film cut off from the product was crushed and dried at 150°C to remove moisture. The dried crushed film was melted in an extruder, extruded from a die in the form of strands, and rapidly cooled and solidified with cold water. The solidified strands were pelletized by a strand cutter. After cutting into a pellet shape, the surface was dried to prevent fusion, and a self-recovering polyethylene terephthalate resin C (hereinafter, resin C) having an intrinsic viscosity of 0.50 dl / g was obtained.

[0118] (Production Example 4: Self-recovery polyethylene terephthalate resin D) The edge rolls and non-standard products generated in the slitting process were washed and peeled off outside. The resulting film with the coating layers peeled off from both surfaces was crushed and dried at 150°C to remove moisture. The dried crushed film was melted in an extruder, extruded from a die in the form of strands, and rapidly solidified with cold water. The solidified strands were cut into pellets with a strand cutter, and the surface was dried to prevent fusion, to obtain a self-recovering polyethylene terephthalate resin D (hereinafter referred to as resin D) with an intrinsic viscosity of 0.60 dl / g.

[0119] (Production Example 5: Coating solution X1: Preparation of adhesive property modifying coating solution) (Polymerization of polyester resin) A stainless steel autoclave equipped with a stirrer, a thermometer, and a partial reflux condenser was charged with 194.2 parts by mass of dimethyl terephthalate, 184.5 parts by mass of dimethyl isophthalate, 14.8 parts by mass of dimethyl-5-sodium sulfoisophthalate, 233.5 parts by mass of diethylene glycol, 136.6 parts by mass of ethylene glycol, and 0.2 parts by mass of tetra-n-butyl titanate, and the transesterification reaction was carried out at a temperature of 160°C to 220°C for 4 hours. The temperature was then raised to 255°C, the reaction system was gradually depressurized, and the reaction was carried out for 1 hour and 30 minutes under a reduced pressure of 30 Pa to obtain a copolymer polyester resin (D-1). The obtained copolymer polyester resin was pale yellow and transparent. The reduced viscosity of the copolymer polyester resin was measured and found to be 0.70 dl / g. The glass transition temperature measured by DSC was 40°C.

[0120] (Preparation of Polyester Water Dispersion) In a reactor equipped with a stirrer, a thermometer, and a reflux device, 30 parts by mass of the polyester resin and 15 parts by mass of ethylene glycol n-butyl ether were placed, and the mixture was heated to 110°C and stirred to dissolve the resin. After the resin was completely dissolved, 55 parts by mass of water was gradually added to the polyester solution while stirring. After the addition, the liquid was cooled to room temperature while stirring to produce a milky white polyester water dispersion with a solid content of 30% by mass.

[0121] (Preparation of aqueous polyvinyl alcohol solution) 90 parts by mass of water was placed in a vessel equipped with a stirrer and a thermometer, and 10 parts by mass of polyvinyl alcohol resin (manufactured by Kuraray) with a degree of polymerization of 500 was gradually added while stirring. After the addition, the liquid was heated to 95°C while stirring to dissolve the resin. After dissolution, the liquid was cooled to room temperature while stirring to prepare an aqueous polyvinyl alcohol solution with a solid content of 10% by mass.

[0122] (Polymerization of Blocked Polyisocyanate Crosslinking Agent) A flask equipped with a stirrer, a thermometer, and a reflux condenser was charged with 100 parts by mass of a polyisocyanate compound having an isocyanurate structure made from hexamethylene diisocyanate (Asahi Kasei Chemicals, Duranate TPA), 55 parts by mass of propylene glycol monomethyl ether acetate, and 30 parts by mass of polyethylene glycol monomethyl ether (average molecular weight 750), and the mixture was kept at 70°C for 4 hours under a nitrogen atmosphere. Thereafter, the reaction liquid temperature was lowered to 50°C, and 47 parts by mass of methyl ethyl ketoxime was added dropwise. The infrared spectrum of the reaction liquid was measured to confirm that the absorption of the isocyanate group had disappeared, and a blocked polyisocyanate aqueous dispersion with a solid content of 75% by mass was obtained.

[0123] The following coating materials were mixed to prepare coating solution X1. Water 40.75% by mass Isopropanol 25.00% by mass Polyester water dispersion 10.32% by mass Polyvinyl alcohol aqueous solution 20.82% by weight Blocked polyisocyanate crosslinking agent 0.50% by mass Particles 1.24% by mass (Silica sol with average particle size of 100 nm, solid content concentration of 40% by mass) Particles 0.74% by mass (Silica sol with average particle size of 450 nm, solid content concentration of 4% by mass) catalyst (Organotin compound solids concentration 14% by mass) 0.48% by mass Surfactant: 0.15% by mass (Silicone-based, solid content 10% by mass)

[0124] (Production Example 6: Coating Solution Y: Preparation of Water-Based Coating Solution) The following coating materials were mixed to prepare coating solution Y. Water 70.64% by mass Isopropanol 9.25% by weight Polyester water dispersion 15.00% by mass Particles 3.41% by mass (Silica sol with average particle size of 100 nm, solid content concentration of 20% by mass) Particles 1.70% by mass (Silica sol with average particle size of 450 nm, solid content concentration of 4% by mass)

[0125] (Production Example 7: Coating Liquid X2: Preparation of Adhesive Modifier Coating Liquid) The following coating materials were mixed to prepare coating solution X2. Water 54.89% by mass Isopropanol 15.00% by mass Polyester water dispersion 18.19% by mass Blocked polyisocyanate crosslinking agent 2.08% by mass Zinc oxide particles 9.37% by mass (Taki Chemical's Ceramace S-8, solids concentration 8% by mass) Particles 0.17% by mass (Silica sol with average particle size of 500 nm, solid content concentration of 15% by mass) Surfactant: 0.30% by mass (Silicone-based, solid content 10% by mass)

[0126] (Production Example 8: Coating Solution X3: Preparation of Adhesive Modifier Coating Solution) (Polymerization of carbodiimide crosslinking agents) In a flask equipped with a stirrer, a thermometer, and a reflux condenser, 168 parts by mass of hexamethylene diisocyanate and 220 parts by mass of polyethylene glycol monomethyl ether (M400, average molecular weight 400) were charged and stirred at 120°C for 1 hour. 26 parts by mass of benzene diisocyanate and 3.8 parts by mass of 3-methyl-1-phenyl-2-phosphorene-1-oxide (2% by weight based on the total isocyanate) as a carbodiimide catalyst. The mixture was added and stirred at 185°C for an additional 5 hours under a nitrogen stream. The infrared spectrum of the reaction solution was measured, and it was confirmed that the absorption at wavelengths of 2200 to 2300 cm-1 had disappeared. The mixture was allowed to cool to 60°C, and 567 parts by mass of ion-exchanged water was added to obtain a carbodiimide-based crosslinking agent with a solid content of 40% by mass.

[0127] The following coating materials were mixed to prepare coating solution X3. Water 48.27% by mass Isopropanol 25.00% by mass Polyester water dispersion 20.09% by mass Carbodiimide crosslinking agent 2.86% by mass Zirconium oxide particles 1.88% by mass (Nissan Chemical ZR-40BL, solid content 40% by mass) Particles 1.60% by mass (Silica sol with average particle size of 450 nm, solid content concentration of 4% by mass) Surfactant: 0.30% by mass (Silicone-based, solid content 10% by mass)

[0128] Example 1 As the raw material for the intermediate layer of the base film, 81 parts by mass of resin A containing no particles, 9 parts by mass of resin C, and 10 parts by mass of resin B containing an ultraviolet absorber were dried under reduced pressure (1 Torr) at 135 ° C for 6 hours, and then fed to extruder 2 (for intermediate layer II), and resin A was dried by a conventional method and fed to extruder 1 (for surface layer I and surface layer III), respectively, and dissolved at 285 ° C. These two layers of polymer were filtered with a stainless steel sintered filter medium (nominal filtration accuracy 10 μm particle 95% cut), laminated in a two-kind three-layer merging block, extruded from a die in the form of a sheet, and then wound around a casting drum with a surface temperature of 30 ° C. using an electrostatic casting method, cooled and solidified, and an unstretched film was produced. At this time, the discharge amount of each extruder was adjusted so that the thickness ratio of layer I, layer II, and layer III was 8:84:8. Furthermore, the intrinsic viscosity of the resin forming layers I and III was 0.65 dl / g, and the intrinsic viscosity of the resin forming layer II was 0.60 dl / g, as determined by an installed online viscometer.

[0129] Then, the unstretched film was coated on both sides by the reverse roll method so that the coating amount after drying was 0.1 g / m 2 The adhesiveness modifying coating solution X1 was applied to the film in the range of width that would remain in use as a product even after slitting, excluding both ends in the film width direction, so that the adhesiveness modifying coating solution X1 was applied to the film in the range of width that would remain in use as a product even after slitting, and then the film was dried at 80° C. for 20 seconds.

[0130] After slitting both ends of the unstretched film on which this coating layer was formed, the film was coated with a coating amount of 0.07 g / m2 after drying at a position 50 to 100 mm from the end, which is mainly a range not coated with the adhesive property modifying coating liquid X1. 2 At this time, the coating was performed so as not to overlap the coating layer of the above-mentioned Coating Liquid X1 as much as possible.

[0131] The unstretched film, the ends of which were coated with the aqueous coating solution, was introduced into a tenter stretching machine, and while the ends of the film were held by clips, it was introduced into a hot air zone at a temperature of 125°C and stretched 4.0 times in the width direction. Next, while maintaining the width stretched in the width direction, it was treated at a temperature of 225°C for 30 seconds, and further subjected to a 3% relaxation treatment in the width direction to obtain a uniaxially oriented PET film with a film thickness of about 100 μm. The intrinsic viscosity of the obtained film was 0.61 dl / g, the number of whiskers on the slit end surface was small, and the film permeability was good. Other film properties are shown in Table 1 below.

[0132] Example 2 A uniaxially oriented PET film with a thickness of about 100 μm was obtained in the same manner as in Example 1, except that the resin composition ratio supplied to the extruder 2 (for the intermediate layer II) was 86 parts by mass of resin A, 4 parts by mass of resin C, and 10 parts by mass of resin B. The intrinsic viscosity of the obtained film was 0.63 dl / g, the number of whiskers on the slit end surface was small, and the film permeability was good. Other film properties are shown in Table 1 below.

[0133] Example 3 The resin composition ratio supplied to extruder 2 (for intermediate layer II) is 72 parts by mass of resin A and 18 parts by mass of resin C. A uniaxially oriented PET film with a thickness of about 100 μm was obtained in the same manner as in Example 1, except that the resin A was 10 parts by mass and the resin B was 10 parts by mass. The intrinsic viscosity of the obtained film was 0.58 dl / g, the number of whiskers on the slit end surface was small, and the film permeability was good. Other film properties are shown in Table 1 below.

[0134] Example 4 A uniaxially oriented PET film having a thickness of about 100 μm was obtained in the same manner as in Example 1, except that the resin composition ratio supplied to the extruder 2 (for the intermediate layer II) was 90 parts by mass of resin A and 10 parts by mass of resin C. The intrinsic viscosity of the obtained film was 0.62 dl / g, the number of whiskers on the slit end surface was small, and the film permeability was good. Other film properties are shown in Table 1 below.

[0135] Example 5 A uniaxially oriented PET film was obtained in the same manner as in Example 1, except that the thickness of the finished film was 60 μm. The intrinsic viscosity of the obtained film was 0.59 dl / g, the number of whiskers on the slit end surface was small, and the film permeability was good. Other film properties are shown in Table 1 below.

[0136] Example 6 A uniaxially oriented PET film was obtained in the same manner as in Example 1, except that the discharge rate of each extruder was adjusted so that the thickness ratio of the I layer, II layer, and III layer was 5:90:5. The intrinsic viscosity of the obtained film was 0.57 dl / g, the number of whiskers on the slit end surface was small, and the film permeability was good. Other film properties are shown in Table 1 below.

[0137] Example 7 A uniaxially oriented PET film was obtained in the same manner as in Example 1, except that the discharge rate of each extruder was adjusted so that the thickness ratio of the I layer, II layer, and III layer was 10:80:10. The intrinsic viscosity of the obtained film was 0.63 dl / g, the number of whiskers on the slit end surface was small, and the film permeability was good. Other film properties are shown in Table 1 below.

[0138] Example 8 A uniaxially oriented PET film was obtained in the same manner as in Example 1, except that the resin composition ratio supplied to the extruder 2 (for the intermediate layer II) was 76 parts by mass of resin A, 14 parts by mass of resin D, and 10 parts by mass of resin B. The intrinsic viscosity of the obtained film was 0.62 dl / g, the number of whiskers on the slit end surface was small, and the film permeability was good. Other film properties are shown in Table 1 below.

[0139] Example 9 A uniaxially oriented PET film was obtained in the same manner as in Example 1, except that the resin composition ratio supplied to the extruder 2 (for the intermediate layer II) was 67 parts by mass of resin A, 9 parts by mass of resin C, 14 parts by mass of resin D, and 10 parts by mass of resin B. The intrinsic viscosity of the obtained film was 0.63 dl / g, the number of whiskers on the slit end surface was small, and the film passing property was also good. Other film properties are shown in Table 1 below.

[0140] Comparative Example 1 The resin composition ratio supplied to extruder 2 (for intermediate layer II) was 90 parts by mass of resin A and 10 parts by mass of resin B, and a uniaxially oriented PET film with a film thickness of about 100 μm was obtained in the same manner as in Example 1. During the resin extrusion, the intrinsic viscosity of the resin forming layer II was 0.64 dl / g, and the intrinsic viscosity of the obtained film was 0.67 dl / g, and the film permeability was good. However, there were many whiskers on the slit end surface. Other film properties are shown in Table 2 below.

[0141] Example 10 The resin composition ratio fed to extruder 2 (for intermediate layer II) was 63 parts by mass of resin A, 27 parts by mass of resin C, and 10 parts by mass of resin B, and a uniaxially oriented PET film with a film thickness of about 100 μm was obtained in the same manner as in Example 1. During resin extrusion, the intrinsic viscosity of the resin forming layer II was 0.55 dl / g, and the intrinsic viscosity of the obtained film was 0.54 dl / g, and although there was some dissatisfaction in terms of film permeability and thickness fluctuation rate, there was little whisker-like material on the end surface after slitting. Other film properties are shown in Table 2 below.

[0142] Example 11 The resin composition ratio fed to extruder 2 (for intermediate layer II) was 63 parts by mass of resin A, 27 parts by mass of resin D, and 10 parts by mass of resin B, and a uniaxially oriented PET film with a film thickness of about 100 μm was obtained in the same manner as in Example 1. The intrinsic viscosity of the obtained film was 0.61 dl / g, and although there was some dissatisfaction in terms of the thickness variation rate and yellowness, there was little whisker-like material on the end surface after slitting. Other film properties are shown in Table 2 below.

[0143] Example 12 A uniaxially oriented PET film with a film thickness of about 100 μm was obtained in the same manner as in Example 1, except that the water-based coating liquid was not applied to both ends of the unstretched film, the coating width of the adhesiveness modifying coating liquid X1 was expanded, and the coating was applied to the positions of both ends where the water-based coating liquid Y was applied, and the water-based coating liquid Y was not applied. The intrinsic viscosity of the obtained film was 0.60 dl / g. Although there was some dissatisfaction in terms of film permeability, there was little whisker-like material on the end surface after slitting. Other film properties are shown in Table 2 below.

[0144] Example 13 A uniaxially oriented PET film was obtained in the same manner as in Example 1, except that the discharge rate of each extruder was adjusted so that the thickness ratio of the I layer, II layer, and III layer was 3:94:3. The intrinsic viscosity of the obtained film was 0.59 dl / g, and the film permeability was also good. Although the haze and yellowness of the film were somewhat unsatisfactory, there was little whisker-like material on the end surface after slitting. Other film properties are shown in Table 2 below.

[0145] Comparative Example 2 A uniaxially oriented PET film was obtained in the same manner as in Example 1, except that the discharge rate of each extruder was adjusted so that the thickness ratio of the I layer, II layer, and III layer was 14:72:14. The intrinsic viscosity of the obtained film was 0.63 dl / g, and the film permeability was also good. However, the number of whiskers on the slit end surface was large. Other film properties are shown in Table 2 below.

[0146] Example 14 The wire bar coating method was used to coat both sides of unstretched film with a dry coating weight of 0.15 g / m 2 A uniaxially oriented PET film was obtained in the same manner as in Example 1, except that the adhesiveness modifying coating solution X2 was applied instead of the adhesiveness modifying coating solution X1 in the range of the width to be used as a product even after slitting, excluding both ends in the film width direction. The intrinsic viscosity of the obtained film was 0.57 dl / g, the number of whiskers on the slit end surface was small, and the film permeability was good. Other film properties are shown in Table 2 below.

[0147] Example 15 The wire bar coating method was used to coat one side of an unstretched film with a coating weight of 0.10 g / m2 after drying. 2 On the other side, replace the adhesiveness modifying coating solution X1 so that the coating amount after drying is 0.08 g / m 2 A uniaxially oriented PET film was obtained in the same manner as in Example 1, except that the adhesiveness modifying coating solution X3 was applied to the film in the width range that will be used as a product after slitting, excluding both ends in the width direction of the film, so that the adhesiveness modifying coating solution X3 was applied to the film in the width range that will be used as a product after slitting. The viscosity was 0.57 dl / g, the number of whiskers on the slit end surface was small, and the film permeability was good. Other film properties are shown in Table 2 below.

[0148] Tables 1 and 2 summarize various film properties of the polyester films of Examples 1 to 15 and Comparative Examples 1 and 2.

[0149] [Table 1]

[0150] [Table 2] [Industrial Applicability]

[0151] According to the present invention, a polyester film roll having less whiskers on the slit end surface can be provided, and the factors that cause defects can be reduced, so that the film can be more applicable to optical applications, particularly to polarizer protective films. Furthermore, by using the polyester film of the present invention as a polarizer protective film, it is possible to provide a polarizing plate or liquid crystal display device that can contribute to reducing the thickness and cost of the display device without reducing visibility due to rainbow spots.

Claims

[Claim 1] A polyester film in which the number of whisker-like particles protruding 5 μm or more on the edge face of a film slit along the machine flow direction during film production is one or less per 100 μm of film length, and the thickness variation rate in the width direction is 5% or less.

Citation Information

Patent Citations

  • Recyclable polyester film

    JP2013039764A

  • Manufacturing method and manufacturing device of optical film

    JP2017109262A

  • Liquid crystal display device, polarizing plate and polarizer protective film

    WO2011162198A1